The development and evaluation of a training monitoring system for amateur rugby union. - Griffin, A.; Kenny, I. C.; Comyns, T. M.; Lyons, M. (Journal of Australian Strength and Conditioning, 2020)
A training monitoring system (TMS) should be both attainable and scientifically grounded, however the optimal method of monitoring training is not yet fully understood. The purpose of this study was to develop and evaluate an online TMS for amateur Rugby Union.